Proximate analysis and anti-proliferative properties of vitex negundo L. - Rabeta Mohd Salleh; Neda Ganjali Dashti; Ong, Ming Thong (Universiti Kebangsaan Malaysia, 2014)
The study of the proximate analysis on the leaves of Vitex negundo L. (VN) was done to gain the preliminary data of the anti-proliferative properties on cancer cell lines. Aqueous and organic extracts of the leaves of VN were used to identify its cytotoxic effect on six types of cancer-origin and normal cells, namely hormone-dependent breast cancer cell line (MCF-7), non-hormone-dependent breast cancer cell line (MDA-MB-231), ovarian cancer cell line (Caov-3), cervical cancer cell line (HeLa), liver cancer cell line (HepG2) and human foreskin fibroblast cell line (Hs27). The anti-proliferation activities of these extracts were investigated by employing colorimetric MTT (3-(4,5-dimethylthiazol-2-yl)2,5 diphenyltetrazolium bromide) assay through time periods of 24, 48 and 72 h. Preliminary results showed that the methanol extracts had significant effects (p<0.05) on MDA-MB-231 with IC50 values 65.38 μg/mL. The nutritional composition of the leaves provides a strong basis for emphasizing the nutritional value of Vitex negundo L.